2020
DOI: 10.1111/jvim.15756
|View full text |Cite|
|
Sign up to set email alerts
|

A multicenter randomized controlled trial of medium‐chain triglyceride dietary supplementation on epilepsy in dogs

Abstract: Background: Medium-chain triglyceride (MCT) enriched diet has a positive effect on seizure control and behavior in some dogs with idiopathic epilepsy (IE).Objective: To evaluate the short-term efficacy of MCTs administered as an add-on dietary supplement (DS) to a variable base diet to assess seizure control and antiseizure drug's (ASD) adverse effect profiles.Animals: Twenty-eight dogs with International Veterinary Epilepsy Task Force Tier II (IVETF) level diagnosis of treated IE with 3 or more seizures in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 86 publications
3
32
0
3
Order By: Relevance
“…Evidence for the efficacy of MCT supplementation to the diets of dogs with IE is increasing, with reductions in epileptic seizures, behavioral and cognitive comorbidities both when combined within a kibble diet [56][57][58] and when added as a supplement to a dog's base diet. 59,60 Understanding the mechanisms behind these positive effects (eg, impacts on the dog microbiome and metabolome 61 ), and identifying profiles of dogs most likely to respond to this dietary intervention is a future priority for MCT research. Evidence for CBD oil supplementation in dogs with IE is in its relative infancy, with a preliminary randomized control study indicating that although the CBD-treated group had a 33% decrease in the group median for mean monthly seizure frequency compared with the placebo-treated group, the proportion of dogs considered treatment "responders" (ie, ≥50% decrease in seizure activity) was similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the efficacy of MCT supplementation to the diets of dogs with IE is increasing, with reductions in epileptic seizures, behavioral and cognitive comorbidities both when combined within a kibble diet [56][57][58] and when added as a supplement to a dog's base diet. 59,60 Understanding the mechanisms behind these positive effects (eg, impacts on the dog microbiome and metabolome 61 ), and identifying profiles of dogs most likely to respond to this dietary intervention is a future priority for MCT research. Evidence for CBD oil supplementation in dogs with IE is in its relative infancy, with a preliminary randomized control study indicating that although the CBD-treated group had a 33% decrease in the group median for mean monthly seizure frequency compared with the placebo-treated group, the proportion of dogs considered treatment "responders" (ie, ≥50% decrease in seizure activity) was similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that administration of EKSs-generated therapeutic ketosis may evoke beneficial effects on CNS diseases [ 34 , 38 , 39 ]. For example, KEs, KSs and MCT oils can evoke anti-seizure and anti-epileptic effects [ 36 , 40 , 41 , 42 ], anxiolytic influence [ 26 , 43 , 44 ], regeneration of nervous system injuries [ 45 ] and alleviating effects on neurodegenerative diseases (such as Alzheimer’s disease) [ 41 , 46 , 47 , 48 ]. These beneficial effects were induced likely through ketosis-evoked neuroprotective effects, for example, by improved mitochondrial functions, enhanced ATP levels, decreased inflammatory processes and decreased oxidative stress [ 23 , 24 , 34 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EKSs are well-tolerated and can generate therapeutic ketosis (ketone levels = 1–7 mM) while maintaining a normal diet ( Clarke et al, 2012 ; Hashim and VanItallie, 2014 ; Ari et al, 2016 ; Stubbs et al, 2017 ). Consequently, EKS administration-generated therapeutic ketosis may be a safe alternative method ( D’Agostino et al, 2013 ; Ari et al, 2016 ; Stubbs et al, 2017 ) to circumvent dietary restrictions and adverse effects by KDs (e.g., nephrolithiasis, growth retardation, constipation, and hyperlipidemia) ( Branco et al, 2016 ) and to treat not only several CNS diseases, such as epilepsy, psychiatric diseases (e.g., anxiety), neurodegenerative disorders (e.g., Alzheimer’s disease), and cancer ( Newport et al, 2015 ; Kovács et al, 2017 , 2019a ; Berk et al, 2020 ), but also, among others, non-alcoholic fatty liver disease, obesity, cardiovascular disease, glucose intolerance, and type 2 diabetes ( Han et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%